A study on financial performance measurement practices in public sector: a case study of Universiti Teknologi MARA (UiTM) / Mohamed Ali Abd Rahman - Abd Rahman, Mohamed Ali (2002)
The objective of this study is to examine how the Bursary uses UiTM Budget as the main financial performance measurement and to identify other financial performance measurement instruments initiated by the Bursary for financial control purpose. The study finds that the Bursary uses budget mechanism such as deduction, Virement' and additional allocation to ensure all allocation is spent in a target range. It is found that procurement, payment, salary, closing of account and audit queries had initiated by the Bursary for financial control purposes. Other financial performance measurement and budget act as a control mechanism to ensure the Bursary achieves its mission to provide an efficient, fast, accurate, and responsible financial services in line with the objective and mission of UiTM. The Balanced Scorecard Model has been used to link between financial and nonfinancial measurement in the Bursary. The Balanced Scorecard translates the Bursary mission and strategy into tangible objectives and measures. The measures represent a balance between external measures for government agency and customers, and internal measures of critical financial process, innovation, and learning and growth. The measures are a balance between the outcome measure the results from past efforts-and the measures that drive future performance. The findings hope to provide some guidelines into the future financial performance measurement instruments practices in Public Higher Learning Institutions.